Diversity, social goods provision, and performance in the firm - Sara Ellison; Jeffrey Greenbaum; Wallace P. Mullin (Center for Economic Studies and ifo Institute (CESifo), 2010)
The last decade has seen a growing interest among economists on the effect of diversity on the provision of social goods and the stock of social capital. Indeed, in the workplace, cooperation, trust, and other social goods may be important elements of the smooth functioning of an office, but firm owners ultimately care about an office's performance, as reflected in revenues, costs, and profits. We explore this next logical question: how does diversity affect ultimate performance? We have a unique data set from a firm which operates numerous small offices in the United States and abroad. They have provided us with eight years of individual-level employee survey data, which measure quantities such as level of cooperation, as well as office-level measures of diversity and performance over that period. We find some evidence that more homogeneous offices enjoy higher levels of social goods provision but that those offices do not perform any better and may actually perform worse. We speculate that one possible reason that the more homogeneous offices do not perform better despite higher levels of social goods provision is that they do not have as diverse a portfolio of skills, talents, and interests on which to draw.
Keywords: J16; L20; 330; diversity; social goods; Diversity Management; Social Capital; Arbeitsleistung; Unternehmensentwicklung; Schätzung; USA